Search for antibiotic alternatives for prevention of liver abscesses in feedlot cattle - Baca, Giovanna (Kansas State University, 2022)
Liver abscesses are a significant animal health, economic loss, and animal welfare concern for the beef cattle feedlot industry. Liver abscesses occur in feedlot cattle because of a high grain feed diet. The primary causative agent is Fusobacterium necrophorum, a ruminal bacterium that enters portal circulation to reach the liver and causes abscesses. Trueperella pyogenes is the second most common pathogen identified, often in combination with F. necrophorum. Salmonella enterica has also been cultured from liver abscesses of cattle. The most common antibiotic used to prevent liver abscesses is tylosin, a macrolide antibiotic. This antibiotic class is a medically important antimicrobial class to human medicine; therefore, it is currently being regulated by the Veterinary Feed Directive. Because of the potential for emergence and dissemination of antimicrobial resistance associated with continuous administration of tylosin in the feed, there is considerable interest in finding an alternative. The research aimed to evaluate different antibiotic alternatives that are inhibitory to pathogens involved in liver abscesses. The following alternatives were evaluated: Sorghum phenolic compounds, probiotic cultures, medium-chain fatty acids, and essential oils. Antimicrobial activities of the sorghum phenolic compound tested were assessed by agar well diffusion assay. Sorghum phenolic extract was added to the wells in concentrations of 0, 100, 200, 500, 1,000, or 4,000 µg/mL. Plates were incubated for 24 hours, and the diameter of each zone of inhibition was measured. None of the sorghum phenolic compounds evaluated had inhibitory effects on F. necrophorum subsp. necrophorum, F. necrophorum subsp. fundiliforme, T. pyogenes, and S. Lubbock. Probiotics are beneficial microbes that have the capability to improve intestinal health by promoting the development of a healthy microbiota, hindering enteric pathogens from colonizing the intestine, increasing digestive capacity, and improving mucosal immunity. The study evaluated the antimicrobial activities of Bacillus pumilus, Bacillus subtilis, Lactobacillus helveticus, Lactobacillus rhamnosus, Lactobacillus acidophilus 020526, Lactobacillus buchneri 110917, Pediococcus acidilactici 060117, and Pediococcus pentosaceus 032118 against liver abscess-causing pathogens. Antibacterial activities of the culture supernatant of probiotic cultures were determined by agar well diffusion assay. Probiotics culture supernatant with pH adjusted to around 7.0 or unadjusted were added to the wells to determine inhibitions. Plates were incubated for 24 hours, and the diameter of each zone of inhibition was measured. The results indicated that the probiotic cultures had inhibitory effects on S. Lubbock and T. pyogenes. None of the culture supernatants had inhibition against both subspecies of F. necrophorum. The antimicrobial activities of medium-chain fatty acids, caproic acid (C6), caprylic acid (C8), capric acid (C10), alone or in combinations, were evaluated by the microbroth dilution method. Bacterial growth was monitored by measuring absorbance at 600 nm at 6, 12, 24, and 48 hours. From the data reviewed, it can be concluded that the efficacy of organic acids was more effective when used in combination. Essential oils, which are plant-based compounds, contain a wide variety of secondary metabolites that can inhibit or slow the growth of bacteria. Antimicrobial activities of the selected essential oils were assessed by the microbroth dilution method. Bacterial growth was monitored by measuring absorbance at 600 nm at 6, 12, 24, and 48 hours. The results indicated that the tested essential oils had no effect against the primary liver abscess-causing pathogens. Antimicrobial resistance has become a major issue in human and animal health around the world. This study provides momentum for the search of MCFA combinations to be potentially used to prevent liver abscesses in feedlot cattle. However, future studies are warranted.
Keywords: Antimicrobial alternatives; Liver abscesses; Essential oils; Phenolic compounds; Tylosin; Medium chain fatty acids